2013
DOI: 10.5657/kfas.2013.0168
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habits of the Black-edged Sculpin Gymnocanthus herzensteini in the Coastal Waters off Mukho, Gangwondo of Korea

Abstract: The feeding habits of the black-edged sculpin Gymnocanthus herzensteini were studied using 944 specimens collected from February 2011 to January 2012 in the coastal waters off Mukho, Gangwondo, Korea. The G. herzensteini ranged from 11.8 to 36.3 cm in total length (TL). The percentage of empty stomachs in G. herzensteini was 40.2%, and the main prey items were Pisces, Euphausiasea, and Macrura. The smallest size group (11.8-15.0 cm TL) consumed mainly Polychaeta and Amphipoda. The quantity of prey increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sculpin are one of the most abundant species in the East/Japan, Okhotsk, Chukchi, and Bering Seas; they are an important component of marine food webs as both prey and predator and feed on a variety of benthic invertebrates and other fish (Panchenko 2009;Gray et al 2017). Yang et al (2013) reported that in the coastal waters of Korea, the major prey for G. herzensteini as determined by stomach content analyses are fish, euphausiids, and shrimp. In addition, these authors found an ontogenetic dietary shift, such that smaller G. herzensteini (less than 15 cm) feed primarily on benthic invertebrates, including amphipods and polychaetes, and their main dietary change during growth is an increased contribution of other fish to their diets.…”
Section: Characteristics In the Food Web Structure Of Fish Consumersmentioning
confidence: 99%
“…Sculpin are one of the most abundant species in the East/Japan, Okhotsk, Chukchi, and Bering Seas; they are an important component of marine food webs as both prey and predator and feed on a variety of benthic invertebrates and other fish (Panchenko 2009;Gray et al 2017). Yang et al (2013) reported that in the coastal waters of Korea, the major prey for G. herzensteini as determined by stomach content analyses are fish, euphausiids, and shrimp. In addition, these authors found an ontogenetic dietary shift, such that smaller G. herzensteini (less than 15 cm) feed primarily on benthic invertebrates, including amphipods and polychaetes, and their main dietary change during growth is an increased contribution of other fish to their diets.…”
Section: Characteristics In the Food Web Structure Of Fish Consumersmentioning
confidence: 99%
“…The genus Gymnocanthus belongs to the family Cottidae (Nakabo 2013), contains nine species distributed in the northern coasts of the Pacific and the Atlantic Ocean including the adjacent Arctic (Froese and Pauly 2003;Nelson et al 2016;Fricke et al 2019). Among them, Gymnocanthus intermedius and Gymnocanthus herzensteini occurs in cold waters around Korea, Japan, and Russia of the western North Pacific, and are used as fishery resources (Kim et al 2005;Yang et al 2013).…”
mentioning
confidence: 99%